2017
DOI: 10.1038/srep44248
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular α-synuclein induces sphingosine 1-phosphate receptor subtype 1 uncoupled from inhibitory G-protein leaving β-arrestin signal intact

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder. The presence of α-synuclein (α-Syn)-positive intracytoplasmic inclusions, known as Lewy bodies, is the cytopathological hallmark of PD. Increasing bodies of evidence suggest that cell-to-cell transmission of α-Syn plays a role in the progression of PD. Although extracellular α-Syn is known to cause abnormal cell motility, the precise mechanism remains elusive. Here we show that impairment of platelet-derived growth factor-induced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…1, A and C, hatched bars in fractions 1 and 2). The amount of S1P 2 R, another subtype of the receptor known to be expressed in this cell line (28), in the raft fractions was not changed by ␣-Syn(A53T) treatment (Fig. 1B, hatched bars in fraction 2).…”
Section: Expulsion Of S1p 1 R From Lipid Raftsmentioning
confidence: 90%
See 2 more Smart Citations
“…1, A and C, hatched bars in fractions 1 and 2). The amount of S1P 2 R, another subtype of the receptor known to be expressed in this cell line (28), in the raft fractions was not changed by ␣-Syn(A53T) treatment (Fig. 1B, hatched bars in fraction 2).…”
Section: Expulsion Of S1p 1 R From Lipid Raftsmentioning
confidence: 90%
“…We have recently found that extracellular ␣-Syn makes S1P 1 R uncouple from the G i protein in the plasma membranes (28). It is important to determine whether S1P 1 R is also uncoupled from the G i protein on MVEs after ␣-Syn treatment, because continuous activation of S1P 1 R and subsequent transmission of the G i protein signal on MVEs has been proven to be critical for cargo sorting into exosomal intralumenal vesicles (ILVs) (25,33).…”
Section: Role Of Extracellular ␣-Syn As An Uncoupler For S1p 1 R Frommentioning
confidence: 99%
See 1 more Smart Citation
“…) and the inhibition of Sphingosine‐1‐phosphate receptor 1 (S1P1) (Zhang et al . ). In contrast, binding of α‐Syn preformed fibrils to lymphocyte‐activation gene 3 was shown to initiate the transmission of pathological α‐Syn (Mao et al .…”
Section: Cell Models Based On the Treatment With Exogenous α‐Syn Speciesmentioning
confidence: 97%
“…CCR1 is typically microglial and its product participates the recruitment of immune cells, but it is also expressed in the ventral midbrain during development, where it is involved in neuronal differentiation of DA neurons [24]. S1P1 is uncoupled from an inhibitory G-protein by extracellular α-syn, and may therefore play a role in intracellular α-syn accumulation [105].…”
Section: Age-dependent Pathway/go Changesmentioning
confidence: 99%